Expressive Law, Social Norms, and Social Groups. Issue 1 (23rd January 2017) - Nadler, Janice
Abstract : To understand how law works outside of sanctions or direct coercion, we must first appreciate that law does not generally influence individual behavior in a vacuum, devoid of social context. Instead, the way in which people interact with law is usually mediated by group life. In contrast to the instrumental view that assumes law operates on autonomous individuals by providing a set of incentives, the social groups view holds that a person's attitude and behavior regarding any given demand of law are generally products of the interaction of law, social influence, and motivational goals that are shaped by that person's commitments to specific in‐groups. Law can work expressively, not so much by shaping independent individual attitudes as by shaping group values and norms, which in turn influence individual attitudes. In short, the way in which people interact with law is mediated by group life.